2019
DOI: 10.14507/epaa.27.4126
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the opt-out movement: Early evidence for Colorado

Abstract: Testing and accountability measures have continued to expand since the passage of the No Child Left Behind Act in 2001. In addition to school and district accountability, student test scores increasingly formed the foundation of teacher performance metrics. State participation rates exceeded the 95% minimum prescribed by law despite increasing opposition to many testing requirements. However, the rollout of the Common Core aligned PARCC tests in 2015 marked the start of a backlash against state mandated testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…On the other hand, a parent-led opt-out movement in which families remove their children from participation in mandated testing has also grown dramatically since 2015 (Clayton et al, 2019). Although this movement has been modest in scope in most places, in some communities opt-out rates are high, and parents' collective perceived interests, and the frames they use to justify those perceptions, have come to operate as new district-or regional-level modes of reproduction, continually reproducing nonparticipation in tests at the individual level (Morel, 2021).…”
Section: Changementioning
confidence: 99%
“…On the other hand, a parent-led opt-out movement in which families remove their children from participation in mandated testing has also grown dramatically since 2015 (Clayton et al, 2019). Although this movement has been modest in scope in most places, in some communities opt-out rates are high, and parents' collective perceived interests, and the frames they use to justify those perceptions, have come to operate as new district-or regional-level modes of reproduction, continually reproducing nonparticipation in tests at the individual level (Morel, 2021).…”
Section: Changementioning
confidence: 99%
“…Opt-out is a national movement (Pizmony-Levy & Green Saraisky, 2016) based on local efforts as expressed in New York (Hursh, 2019;Wang, 2017), Colorado (Clayton et al, 2019), and Florida (Schroeder et al, 2018). While these and other studies address opt-out demographics (Paquin Morel, 2019) and public perception of the movement (Pizmony- Levy & Cosman, 2017), fewer studies address the political activism that extends beyond the act of refusing specific tests to changing standardized testing policy.…”
Section: Conclusion/recommendationsmentioning
confidence: 99%
“…New York's high opt-out rates, particularly in affluent areas such as Long Island, and the weight of available studies combine to suggest New York forms an epicenter for the opt-out movement. While opt-out is occurring in other states including Florida (Currin et al, 2018;Schroeder et al, 2018) and Colorado (Clayton et al, 2019), Western states in general and Arizona in particular are underrepresented in the literature.…”
Section: Opt-out Movement Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A national survey of opt-out activists from 47 states found that respondents were mostly parents or caregivers of school-aged children and almost half of the activists were teachers or educators (Pizmony-Levy & Green Saraisky, 2016). In a study of the Colorado opt-out movement, researchers used school-level data to demonstrate that widespread participation in opt-out was most prevalent in suburban and rural areas and in higher SES communities with high performing schools (Clayton, Bingham & Ecks, 2019). Additionally, scholars have looked at the role of women in the movement (Schroeder, Currin & McCardle, 2018).…”
Section: The Opt-out Movementmentioning
confidence: 99%